Fabulating Archival Arts: An Exploration of the Complexities of Politics, History, and Memory in a Postmodern Context - Wang, Chenyi (Transactions on Social Science, Education and Humanities Research, 2024)
Archival art, which emerged in the last century, has become a significant influence in the art world, challenging the constraints of traditional historical narratives. It offers viewers a more nuanced and inclusive framework for thinking, providing an alternative engagement with history free from dominant past narratives. This paper undertakes a comprehensive analysis of two significant archival artworks, namely the Atlas Group and Sputnik. Through this analysis, it aims to elucidate the societal impacts engendered by archival art that adopts critical fabulation as a strategy. Combining textual and graphic analyses with perspectives from postmodernism and deconstructionism, the research demonstrates that fictional archival art stimulates profound contemplation of the interconnectedness between the past, present, and future through artistic expression. It also examines the emotional impact of revisiting the past, records, and memory. By navigating the complexities and ambiguities of postmodern society through archival artistic expression, we can foster a more inspiring approach to understanding this art form.